Pengaruh Budaya Organisasi dan Lingkungan Kerja Non Fisik terhadap Kepuasan Kerja Pegawai pada Kantor Kecamatan Tanete Rilau Kab. Barru - Aulya Nur’Rahma; Ikhwan Maulana Haeruddin; Siti Hasbiah; Agung Widhi Kurniawan; Muhammad Ichwan Musa (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of organizational culture and the non-physical work environment on employee job satisfaction at the Tanete Rilau Sub-district Office, Barru Regency. The research adopts an associative quantitative approach with a saturated sampling technique, involving 32 employees as respondents. Data collection was conducted through observation and questionnaires, while data analysis utilized validity and reliability tests, descriptive analysis, multiple regression analysis, the coefficient of determination, classical assumption tests, and hypothesis testing using the Statistical Product and Service Solution (SPSS) software. The findings reveal that organizational culture and the non-physical work environment each have a positive and significant effect on job satisfaction, both partially and simultaneously. The regression results indicate that the non-physical work environment exerts a more dominant influence compared to organizational culture. The coefficient of determination (R²) shows that 41% of the variation in employee job satisfaction is explained by these two variables, while the remaining 59% is influenced by other factors outside the model. These findings emphasize that strengthening a collaborative, communicative, and supportive organizational culture, along with creating a conducive non-physical work environment, are critical strategies for improving employee job satisfaction and ultimately enhancing the quality of public service delivery at the sub-district level. The study contributes practically by providing insights for local government institutions to design policies and interventions that foster motivation, loyalty, and productivity among employees.